Pegasus, the flying horse - Yolen, Jane.; Li, Ming, 1958- (New York : Dutton Children's Books, 1998)
Retells how, with the help of the goddess Athena, the handsome and overly proud Bellerophon tames the winged horse Pegasus and conquers the monstrous Chimaera.
School Library Journal
Publisher's Weekly
Book Report
5.4
3-6
Keywords: Pegasus (Greek mythology) -- Juvenile literature; Pegasus (Greek mythology); Mythology, Greek; Pegasus (Greek mythology); Classical mythology